2006
DOI: 10.1097/01.mej.0000206195.92695.26
|View full text |Cite
|
Sign up to set email alerts
|

Medical education and quality of care in the pediatric emergency department setting: a combined model

Abstract: A combined program of medical education/quality assurance-improvement in the emergency department is feasible and seems to contribute to improved medical services and patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Most of these had 'good' methodological quality. About half these studies showed statistically significant outcomes, specifically in improved diabetes care, preventive care measures, documentation and critical care measures [44][45][46][47][48] ; and the other half did not show statistically significant outcomes. [49][50][51][52] The least common intervention used individual projects in which the trainee worked independently.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Most of these had 'good' methodological quality. About half these studies showed statistically significant outcomes, specifically in improved diabetes care, preventive care measures, documentation and critical care measures [44][45][46][47][48] ; and the other half did not show statistically significant outcomes. [49][50][51][52] The least common intervention used individual projects in which the trainee worked independently.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…In recent years, novel feedback interventions have contributed to notable improvements in patient care, quality metrics, and educational curricula throughout diverse care settings. [23][24][25][26][27][28][29][30][31][32][33][34] Furthermore, a recent Cochrane review examined the type of feedback to include and the most effective process to deliver feedback, recommending use of specific improvement plans and exchange of data between respected colleagues. 35 To our knowledge, follow-up and feedback programs related to pediatric transfers have not been described in the literature to date.…”
mentioning
confidence: 99%
“…The study by Kaddan et al [4] shows that a brief daily intervention of this nature leads to incremental improvement in the knowledge of trainees and the care they provide. Furthermore, the risk management aspects of this cannot be ignored.…”
mentioning
confidence: 99%